Sy123
This too shall pass
- Joined
- Nov 6, 2011
- Messages
- 3,725
- Gender
- Male
- HSC
- 2013
Re: HSC 2014 4U Marathon
y= -(2A/C) x
![](https://latex.codecogs.com/png.latex?\bg_white Ax^2 + B \frac{4A^2x^2}{C^2} + Cx \frac{-2A}{C}x + D = 0 \\ \\ x^2(\frac{4A^2B}{C^2}- A) = -D )
and thus![](https://latex.codecogs.com/png.latex?\bg_white \frac{4A^2B}{C^2} - A \leq 0 )
The idea is spot on, my algebra was thoughNot sure about my inequality result, but I think my solution is wrongView attachment 29810
y= -(2A/C) x
and thus
Last edited: